The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1073/pnas.1705287114
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of human brown adipose tissue in lean and obese young men

Abstract: Human brown adipose tissue (BAT) can be activated to increase glucose uptake and energy expenditure, making it a potential target for treating obesity and metabolic disease. Data on the functional and anatomic characteristics of BAT are limited, however. In 20 healthy young men [12 lean, mean body mass index (BMI) 23.2 ± 1.9 kg/m 2 ; 8 obese, BMI 34.8 ± 3.3 kg/m 2 ] after 5 h of tolerable cold exposure, we measured BAT volume and activity by 18 F-labeled fluorodeoxyglucose positron emission tomography/computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
362
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(397 citation statements)
references
References 43 publications
11
362
0
7
Order By: Relevance
“…Although the relative volume of BAT in humans may be limited compared with skeletal muscle, the uptake of fatty acids per gram tissue by BAT exceeds that by skeletal muscle by >10-fold (figure 3F). Also, a recent paper redefined whole-body BAT distribution in humans and concluded that its metabolic capacity is substantially higher than usually reported 40. The effects of butyrate on fatty acid uptake and oxidation by BAT we observe in mice may thus well be relevant for humans.…”
Section: Discussionmentioning
confidence: 54%
“…Although the relative volume of BAT in humans may be limited compared with skeletal muscle, the uptake of fatty acids per gram tissue by BAT exceeds that by skeletal muscle by >10-fold (figure 3F). Also, a recent paper redefined whole-body BAT distribution in humans and concluded that its metabolic capacity is substantially higher than usually reported 40. The effects of butyrate on fatty acid uptake and oxidation by BAT we observe in mice may thus well be relevant for humans.…”
Section: Discussionmentioning
confidence: 54%
“…It has been reported that higher human in vivo BAT activity changes metabolism through increased energy expenditure . However, the current topic of debate questions whether we fully grasp the complete thermogenic potential of active human BAT . The finding that ZIC1 was positively associated with age and BMI and negatively associated with BAT activity is interesting because, to the best of our knowledge, no links have been established between BAT activity and ZIC1.…”
Section: Discussionmentioning
confidence: 96%
“…Another limitation of the current study is that not all fat is in adipose tissue, and we were unable to adjust our organ mass estimates for nonadipose intracellular triglyceride content . Similarly, we did not build brown fat, a potential source of thermogenesis, into our models . Lastly, we contrasted obesity‐tissue features in men to those observed in our sample of women.…”
Section: Discussionmentioning
confidence: 97%